Boarding House Search Information System Database Design - Muhammad Rehan Anwar; Suryari Purnama (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2022)
Technological advancements are causing humans to produce several inventions and developments to accomplish anything. Which one utilizes internet technology to obtain information as quickly and simply as possible? For example, if someone moves to a new area for work or school, they will need boarding houses. However, this information is difficult to obtain because it is traditionally passed down from person to person, and the boarding house owner finds it difficult to promote his boarding house. As a result, individuals require a computerized system to resolve this issue. This study aims to create a database design for a boarding home information system. This study employs the DBLC (Database Life Cycle) technique, which illustrates the life cycle of a database that may be developed at any time. Database design is separated into three parts: conceptual, logical, and physical database design.